Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 3 \(\frac{14}{19}\)+ \(\frac{13}{17}\)+ \(\frac{35}{43}\)+ 6\(\frac{5}{19}\)+ \(\frac{8}{43}\)= \(\left(3\frac{14}{19}+6\frac{5}{19}\right)+\left(\frac{35}{43}+\frac{8}{43}\right)+\frac{13}{17}=\)\(9+1+\frac{13}{17}=8+\frac{13}{17}=8\frac{13}{17}\)
b, \(\frac{-5}{7}.\frac{2}{11}+\frac{-5}{7}.\frac{9}{11}+1\frac{5}{7}\)\(=\frac{-5}{7}\left(\frac{2}{11}+\frac{9}{11}\right)+1\frac{5}{7}\)\(=\frac{-5}{7}.1+1\frac{5}{7}\)\(=\frac{-5}{7}+\frac{12}{7}=\frac{7}{7}=1\)
Chúc bn học tốt
\(3\frac{14}{19}+\frac{13}{17}+\frac{35}{43}+6\frac{5}{19}+\frac{8}{43}\)
\(=\left(3\frac{14}{19}+6\frac{5}{19}\right)+\left(\frac{35}{43}+\frac{8}{43}\right)+\frac{13}{17}\)
\(=10+1+\frac{13}{17}=11+\frac{13}{17}=11\frac{13}{17}\)
Bài 1:
a) \(\frac{25}{4}+\frac{-5}{4}=\frac{25-5}{4}=\frac{20}{4}=5\)
b)\(\frac{-5}{9}+\left(\frac{-2}{7}\right)=\frac{-35}{63}+\left(\frac{-18}{63}\right)=\frac{-53}{63}\)
c) \(\frac{1}{4}+\frac{9}{11}+\frac{7}{4}+\left(\frac{-2}{11}\right)=\left(\frac{1}{4}+\frac{7}{4}\right)+\left(\frac{-2}{11}+\frac{9}{11}\right)=2+\frac{7}{11}=\frac{22+7}{11}=\frac{29}{11}\)
d) \(\frac{-5}{19}.\frac{8}{19}+\left(\frac{-14}{19}\right).\frac{11}{19}=\frac{-40}{361}-\frac{151}{361}=-\frac{191}{361}\)
Bài 2:
a) \(x+\frac{5}{9}=\frac{-8}{9}\) \(\Leftrightarrow x=\frac{-8}{9}-\frac{5}{9}\) \(\Leftrightarrow x=-\frac{13}{9}\)
b) \(\frac{-1}{8}-x=\frac{9}{20}\) \(\Leftrightarrow x=\frac{-1}{8}-\frac{9}{20}\) \(\Leftrightarrow x=\frac{-5}{40}-\frac{18}{40}\) \(\Leftrightarrow x=-\frac{23}{40}\)
c) (x + 5)3 - 12 = 15
\(\Leftrightarrow\)(x + 5)3 = 27
\(\Leftrightarrow\)x + 5 = 3
\(\Leftrightarrow\)x = -2
d) \(\left|x-3\right|-\frac{4}{15}=\frac{26}{15}\) \(\Leftrightarrow\left|x-3\right|=2\) \(\Leftrightarrow\orbr{\begin{cases}x-3=2\\x-3=-2\end{cases}}\) \(\Leftrightarrow\orbr{\begin{cases}x=5\\x=1\end{cases}}\)
câu a
\(\left(5\dfrac{7}{9}+2\dfrac{3}{11}\right)-\left(-1\dfrac{8}{11}+3\dfrac{7}{9}\right)\)
= \(5\dfrac{7}{9}+2\dfrac{3}{11}+1\dfrac{8}{11}-3\dfrac{7}{9}\)
= \(\left(5\dfrac{7}{9}-3\dfrac{7}{9}\right)+\left(2\dfrac{3}{11}+1\dfrac{8}{11}\right)\)
= \(2+3\dfrac{11}{11}\)
= \(2+3+1\)
= \(6\)
câu b
\(\left(2\dfrac{7}{19}-3\dfrac{8}{9}\right)-\left(1\dfrac{7}{19}-2\dfrac{1}{9}\right)\)
= \(2\dfrac{7}{19}-3\dfrac{8}{9}-1\dfrac{7}{19}+2\dfrac{1}{9}\)
= \(\left(2\dfrac{7}{19}-1\dfrac{7}{19}\right)-\left(3\dfrac{8}{9}-2\dfrac{1}{9}\right)\)
= \(1-1\dfrac{7}{9}\)
= \(\dfrac{-7}{9}\)
a)\(x.6=-72\)
=> x = -12
b)\(\dfrac{7}{3}:x=\dfrac{-11}{45}\)
=> \(x=\dfrac{-105}{11}\)
c) \(x=\dfrac{-17}{9}\)
d)\(x=\dfrac{-3}{17}\)
e) \(x=\dfrac{7}{6}\)
f) \(\dfrac{39}{7}:x=11\)
=> \(x=\dfrac{39}{77}\)
a)
\(\dfrac{x}{8}=\dfrac{-9}{6}\)
=> x = \(\dfrac{8.\left(-9\right)}{6}\)
=> x = -12
Bài 1:
a) Ta có: \(\frac{3}{5}+\frac{4}{15}\)
\(=\frac{9}{15}+\frac{4}{15}\)
\(=\frac{13}{15}\)
b) Ta có: \(\frac{-3}{5}+\frac{5}{7}\)
\(=\frac{-21}{35}+\frac{25}{35}=\frac{4}{35}\)
c) Ta có: \(\frac{5}{6}:\frac{-7}{12}\)
\(=\frac{5}{6}\cdot\frac{-12}{7}=\frac{-60}{42}=\frac{-10}{7}\)
d) Ta có: \(\frac{-21}{24}:\frac{-14}{8}\)
\(=\frac{-7}{8}:\frac{-7}{4}\)
\(=\frac{-7}{8}\cdot\frac{4}{-7}=\frac{4}{8}=\frac{1}{2}\)
e) Ta có: \(\frac{-3}{5}\cdot\frac{5}{7}+\frac{-3}{5}\cdot\frac{3}{7}+\frac{-3}{5}\cdot\frac{6}{7}\)
\(=\frac{-3}{5}\left(\frac{5}{7}+\frac{3}{7}+\frac{6}{7}\right)\)
\(=-\frac{3}{5}\cdot2=\frac{-6}{5}\)
f) Ta có: \(\frac{1}{3}\cdot\frac{4}{5}+\frac{1}{3}\cdot\frac{6}{5}-\frac{4}{3}\)
\(=\frac{1}{3}\cdot\frac{4}{5}+\frac{1}{3}\cdot\frac{6}{5}-\frac{1}{3}\cdot4\)
\(=\frac{1}{3}\left(\frac{4}{5}+\frac{6}{5}-4\right)\)
\(=\frac{1}{3}\cdot\left(-2\right)=\frac{-2}{3}\)
g) Ta có: \(\frac{4}{19}\cdot\frac{-3}{7}+\frac{-3}{7}\cdot\frac{5}{19}+\frac{5}{7}\)
\(=\frac{4}{19}\cdot\frac{-3}{7}+\frac{5}{19}\cdot\frac{-3}{7}+\frac{-3}{7}\cdot\frac{5}{-3}\)
\(=-\frac{3}{7}\left(\frac{4}{19}+\frac{5}{19}+\frac{-5}{3}\right)\)
\(=\frac{-3}{7}\cdot\left(\frac{27}{57}+\frac{-95}{57}\right)\)
\(=\frac{-3}{7}\cdot\frac{-68}{57}=\frac{68}{133}\)
h) Ta có: \(\frac{5}{9}\cdot\frac{7}{13}+\frac{5}{9}\cdot\frac{9}{13}-\frac{5}{9}\cdot\frac{3}{13}\)
\(=\frac{5}{9}\left(\frac{7}{13}+\frac{9}{13}-\frac{5}{13}\right)\)
\(=\frac{5}{9}\)
Dấu " / " là phân số nhé
a) 5/-4 . 16/25 + -5/4 . 9/25
= -5/4 . 16/25 + -5/4 . 9/25
= -5/4 . ( 16/25 + 9/25 )
= -5/4 . 1
= -5/4
b) 4 11/23 - 9/14 + 2 12/23 - 5/4
= 103/23 - 9/14 + 58/23 - 5/4
= 103/23 + 58/23 - 9/14 - 5/4
= 7 - 9/14 - 5/4
= 143/28
c) 2 13/27 - 7/15 + 3 14/27 - 8/15
= 67/27 - 7/15 + 95/27 - 8/15
= 67/27 + 95/27 - 7/15 - 8/15
= 6 - 7/15 - 8/15
= 5
a: \(=8^8\left(8^2-8-1\right)=8^8\cdot55⋮5\)
b: \(=7^4\left(7^2+7+1\right)=7^4\cdot57⋮̸11\)
\(9^8=9.9.9.9.9.9.9.9\)
\(5^7=5.5.5.5.5.5.5\)
\(19^7=19.19.19.19.19.19.19\)
\(34^9=34.34.34.34.34.34.34.34.34\)
---------HOK TỐT---------